Pengembangan Aplikasi Asisten Investasi Berbasis Chatbot Android - William Pratama; Jullend Gatc (UNIVERSITAS KALBIS, 2022)
Stocks are a very attractive investment instrument, especially among millennials today. All too tempted when you see a big advantage without learn the basics will be disaster if something goes wrong. This study aims to make novice investors have a place to learn without having to pay by implementing a chatbot application as an intermediary. Chatbots who have knowledge about stock investment are expected to be a good support system for investors beginners, and can be used anywhere and anytime without a time limit. In making chatbot researchers using the dialogueflow platform. The output of this research is an android application called my assistant. System development is carried out using the prototyping method and Unified Modeling Language (UML) as the model. Based on research testing and evaluation, the system created can interact well without any problems.